2011
DOI: 10.1007/s11255-010-9880-y
|View full text |Cite
|
Sign up to set email alerts
|

Alternative management of complex renal stones

Abstract: This series demonstrates that ureterorenoscopy and Holmium laser lithotripsy is an effective and safe primary treatment modality for the treatment of large complex kidney stones. It is an attractive alternative to PCNL, particularly in those with comorbid conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Staghorn calculi are branched stones that fill the renal pelvis and branch into several or all of the calices [7,8]. Despite the widespread appeal of PCNL in the management of large-volume renal stones, its application in patients with staghorn calculi is one of the more challenging endourologic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Staghorn calculi are branched stones that fill the renal pelvis and branch into several or all of the calices [7,8]. Despite the widespread appeal of PCNL in the management of large-volume renal stones, its application in patients with staghorn calculi is one of the more challenging endourologic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that as the size of the stone increases, and as the complexity of the situation increases, the stone-free rate decreases. 35,36 Residual stone of varying size was seen in 15 (14.1%) cases. Re-PCNL was required in 1 patient, while 1 patient required URSL in whom the stone had descended into the ureter, and ESWL was given to 13 (12.1%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…19,37,39,42,44,45 This decreased to 25%-75% when stones greater than 4 cm were treated. 20,38,39,41,47,48 Ricchiuti et al's study of 23 patients' SFR dropped from 88% to 60% to 40% for stone sizes 2-3 cm, 3-4 cm, and above 4 cm, respectively. 47 Mariani did report an overall SFR of 95% for stones ranging from 2 to 10 cm, but required an average of 1.7 procedures per patient.…”
Section: Effects Of Obesity On Outcomesmentioning
confidence: 92%
“…25,37 Recent studies have reported the successful treatment of stones greater than 2 cm with flexible URS. 19,20,[37][38][39][40][41][42][43][44][45][46][47][48][49] One limitation of the current literature related to stone treatment is the lack of a standardized definition of stone-free. The definition of less than 4 mm on imaging not requiring a second procedure was used here as a standardized comparison between studies.…”
Section: Effects Of Obesity On Outcomesmentioning
confidence: 99%